Петр Тимофеевич Фомин - Сазонова Кира Константиновна (Художник РСФСР, 1984)
Экземпляры: ИСК (20121005) / Инвентарный номер: 819382 / Цена: 8.30 / Сис.шифр: 85.143(2)7-8 / Авт.знак: С 14 / ГРНТИ: 18.31.31 / ББК: 85.143(2)7-8